Heme (dys)homeostasis and liver disease - Duarte, Tiago L.; Viveiros, Nicole; Godinho, Catarina; Duarte, Delfim (Frontiers in Physiology, 2024)
Heme is essential for a variety of proteins involved in vital physiological functions in the body, such as oxygen transport, drug metabolism, biosynthesis of steroids, signal transduction, antioxidant defense and mitochondrial respiration. However, free heme is potentially cytotoxic due to the capacity of heme iron to promote the oxidation of cellular molecules. The liver plays a central role in heme metabolism by significantly contributing to heme synthesis, heme detoxification, and recycling of heme iron. Conversely, enzymatic defects in the heme biosynthetic pathway originate multisystemic diseases (porphyrias) that are highly associated with liver damage. In addition, there is growing evidence that heme contributes to the outcomes of inflammatory, metabolic and malignant liver diseases. In this review, we summarize the contribution of the liver to heme metabolism and the association of heme dyshomeostasis with liver disease.